Tumor-Expressed IDO Recruits and Activates MDSCs in a Treg-Dependent Manner - Holmgaard, Rikke B.; Zamarin, Dmitriy; Li, Yanyun; Gasmi, Billel; Munn, David H.; Allison, James P.; Merghoub, Taha; Wolchok, Jedd D. (Cell reports (Cambridge), 2015)
Indoleamine 2,3-dioxygenase (IDO) has been described as a major mechanism of immunosuppression in tumors, though the mechanisms of this are poorly understood. Here, we find that expression of IDO by tumor cells results in aggressive tumor growth and resistance to T-cell-targeting immunotherapies. We demonstrate that IDO orchestrates local and systemic immunosuppressive effects through recruitment and activation of myeloid-derived suppressor cells (MDSCs), through a mechanism dependent on regulatory T cells (Tregs). Supporting these findings, we find that IDO expression in human melanoma tumors is strongly associated with MDSC infiltration. Treatment with a selective IDO inhibitor in vivo reversed tumor-associated immunosuppression by decreasing numbers of tumor-infiltrating MDSCs and Tregs and abolishing their suppressive function. These findings establish an important link between IDO and multiple immunosuppressive mechanisms active in the tumor microenvironment, providing a strong rationale for therapeutic targeting of IDO as one of the central regulators of immune suppression. [Display omitted] •Tumor IDO mediates local/systemic immunosuppression and resistance to immunotherapy•IDO expression in human and mouse tumors is associated with MDSC infiltration•Tumor IDO induces immunosuppression by expanding, recruiting, and activating MDSCs•Tumor-IDO-mediated recruitment and activation of MDSCs are Treg dependent IDO mediates immune inhibition in tumors, though the mechanisms of this are poorly understood. Holmgaard et al. demonstrate that tumor IDO is a central regulator of both local and systemic immunosuppression and resistance to immunotherapy, which is orchestrated through expansion, recruitment, and activation of MDSCs in a Treg-dependent manner.